P105 Complications of incisional hernia repair after orthotopic liver transplantation. (16th November 2010) - Hoare, M; Callaghan, C; Gibbs, P
Abstract : Introduction: Incisional hernia is common after liver transplantation (LT) affecting between 5–23% of recipients. Operative repair is feasible but complications may be increased given co-morbidity in LT recipients. Hernia recurrence rates after repair range between 16–50% in other series. Method: A retrospective review of incisional herniorrhaphy identified from our institutional LT database was conducted to determine post-operative complication and recurrence rates. Complications were categorised into chest: PE, chest sepsis, re-intubation; Renal: acute renal failure defined by RIFLE criteria, requirement for RRT and one year follow-up renal function; Wound: wound infection by clinical or microbiological diagnosis. Hernia recurrence was defined by clinical or radiological diagnosis. Results: Sixty-nine herniorrhaphy procedures were identified in 59 individuals (38 male (64%); mean age 59.3 (range (25.9–77.6)); 16 (23%) diabetics) performed at a median 1053 days (range 130–6932) after LT Median length of in-hospital stay was 7 days (range 1–33). There were no liver-related complications. Chest sepsis occurred in 13 of 69 (19%) cases; 12 settled with antibiotics; 1 patient with cystic fibrosis required mechanical ventilation. There were no pulmonary emboli. There was a significant rise in creatinine from pre-operative median of 102 μM (57–545 μM) to post-operative of 125 μM (75–575 μM) (p <0.0001). However, one year follow-up creatinine (101 μM (49–563 μM) was not different to preoperative values (p =0.16); 9 of 69 (13%) cases were complicated by a 50% rise in creatinine, 1 case by a 100% rise and 1 case by 200% rise in creatinine. Restricting analysis to subjects with pre-existing renal impairment revealed a significant rise in post-operative creatinine (p =0.0023), but no change in one year follow-up creatinine values (p =0.17). No patient required initiation of RRT. Wound infection occurred in 6 of 69 (9%) cases; 1 required operative drainage.3 patients suffered long-term wound pain. One patient developed one each of urinary infection, C. difficile -diarrhoea and wound seroma. After each repair subjects were followed for a median 928 days (range 18–3323). 18/69 (26%) procedures were complicated by recurrent hernia at a median of 407 days (6–1572) of which 2 were incarcerated. Kaplan-Meier analysis determined a 1, 2 and 3 year hernia-free survival of 87%, 74% and 72% respectively. Conclusion: There were significant rates of chest and renal complications following incisional herniorrhaphy in liver transplant recipients, but few long-term sequelae. Incisional hernia repair was complicated by a 26% 2-year recurrence rate.